2015
DOI: 10.3390/ijms160714526
|View full text |Cite
|
Sign up to set email alerts
|

Eriodictyol Protects Endothelial Cells against Oxidative Stress-Induced Cell Death through Modulating ERK/Nrf2/ARE-Dependent Heme Oxygenase-1 Expression

Abstract: The pathophysiology of cardiovascular diseases is complex and may involve oxidative stress-related pathways. Eriodictyol is a flavonoid present in citrus fruits that demonstrates anti-inflammatory, anti-cancer, neurotrophic, and antioxidant effects in a range of pathophysiological conditions including vascular diseases. Because oxidative stress plays a key role in the pathogenesis of cardiovascular disease, the present study was designed to verify whether eriodictyol has therapeutic potential. Upregulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 46 publications
(52 reference statements)
3
46
0
4
Order By: Relevance
“…Then, an integrated in silico approach was applied to decipher the 42 targets for these active ingredients related to BSS including 27 common targets, which distinctly explained the action modes and biological processes that active ingredients achieve their synergistic and complementary curative effects. It is worth mentioning that the results from several compound-target interaction experiments by us and other groups indicated the reasonability of our integrated in silico approach4546474849505173. Subsequently, 20 signaling pathways associated with BSS treatment and prophylaxis by Danggui-Honghua were retrieved.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Then, an integrated in silico approach was applied to decipher the 42 targets for these active ingredients related to BSS including 27 common targets, which distinctly explained the action modes and biological processes that active ingredients achieve their synergistic and complementary curative effects. It is worth mentioning that the results from several compound-target interaction experiments by us and other groups indicated the reasonability of our integrated in silico approach4546474849505173. Subsequently, 20 signaling pathways associated with BSS treatment and prophylaxis by Danggui-Honghua were retrieved.…”
Section: Discussionmentioning
confidence: 94%
“…For example, in animal models, increased expression of HMOX1 has been shown to protect tissues and cells against ischemia-reperfusion injury, oxidative stress, inflammation and hypoxia-induced vascular stasis47. The protein HMOX1 was found to have interactions with 9 ingredients, and senkyunolide A, kaempferol and eriodictyol synergistically increase HMOX1 expression484950. In addition, the neurotoxic proinflammatory mediator PTGS2 was also connected with several active ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-HIV [2] N/A b-amyrin acetate N/A Anticonvulsant, anti-inflammatory, antinociceptive, antioxidant, antidyslipidaemic [101][102][103] Naringenin 7-O-b-Dglucopyranoside N/A Anti-inflammatory, antioxidant, antiviral, hypoglycaemic, hypolipidaemic, pesticide, hypocholesterolaemic, antifungal, antibacterial [101,104,105] Naringenin N/A Enzyme inhibitors, antioxidants, anticancer, anti-inflammatory, hypocholesterolaemic, antibacterial, hepatoprotective, anti-HIV, antispasmodic, antitumour, antiviral, antiulcer, antileukemic, neuroprotective, antihepatotoxic, antifungal [101] Eriodictyol N/A Anti-inflammatory, antibacterial, antioxidant, antiperoxidant, cancer-preventive, aphidifuge, antifeedant, Anti-osteoclastogenic, antagonist, antinociceptive [101,[106][107][108][109][110][111] N/A, not available. [80] Anti-inflammatory WP OA from methanol extract 1-10 lg/ml FMLP and PMA-induced superoxide anion generation by human neutrophil OA inhibited the superoxide anion generation in response to fMLP [86] L, S 11 phytocompounds from ethanol extract [85] number of OH groups in B-ring of flavanones plays a crucial role in radical scavenging activity.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…It has been demonstrated that HO-1 protects cells from damage induced by oxidative stress in diverse cell types. 40) In addition, HO-1 exerts cytoprotective effects by preventing apoptosis. 40) These findings suggest that HO-1 upregulation by EPS may prevent the development and progression of disorders caused by oxidative stress.…”
Section: )mentioning
confidence: 99%